2023
DOI: 10.3390/ijms24021291
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Hydroxyapatite Composite Scaffolds Loaded with Bioactive Factors and Drugs for Bone Tissue Engineering

Abstract: Nano-hydroxyapatite (n-HAp) is similar to human bone mineral in structure and biochemistry and is, therefore, widely used as bone biomaterial and a drug carrier. Further, n-HAp composite scaffolds have a great potential role in bone regeneration. Loading bioactive factors and drugs onto n-HAp composites has emerged as a promising strategy for bone defect repair in bone tissue engineering. With local delivery of bioactive agents and drugs, biological materials may be provided with the biological activity they l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 197 publications
0
17
0
Order By: Relevance
“…The use of scaffolds has been widespread in biomedical applications for tissue engineering, which involves designing implantable biomimetic structures of organs or in vivo microenvironments, ,, as well as for sustained/controlled drug release. ,,,,, The recent literature has reported scaffolds prepared using synthetic materials (e.g., polymers/polymeric hydrogels) , or naturally derived biomaterials ,, or a combination of both . These materials can exhibit high biocompatibility and biodegradability, and provide a suitable microenvironment for cell growth, proliferation and differentiation, and tissue regeneration enhancement …”
Section: Scaffoldsmentioning
confidence: 99%
“…The use of scaffolds has been widespread in biomedical applications for tissue engineering, which involves designing implantable biomimetic structures of organs or in vivo microenvironments, ,, as well as for sustained/controlled drug release. ,,,,, The recent literature has reported scaffolds prepared using synthetic materials (e.g., polymers/polymeric hydrogels) , or naturally derived biomaterials ,, or a combination of both . These materials can exhibit high biocompatibility and biodegradability, and provide a suitable microenvironment for cell growth, proliferation and differentiation, and tissue regeneration enhancement …”
Section: Scaffoldsmentioning
confidence: 99%
“…Growth factors, synthetic peptides, vitamins (D 3 and K), drugs, and other bioactive substances were employed for bone regeneration in conjunction with nHAp scaffolds. 11 One study demonstrated that the sustained delivery of growth factors increased the production of factors linked to osteogenic differentiation in poly(lactide-co-glycolide) (PLGA) microspheres loaded with vascular endothelial growth factors and bone morphogenic protein-2 (BMP-2) containing collagen and n-HAp. 12 Recent research using nHAp and polydopamineassisted coating of BMP-2-derived peptides shows considerably greater in vitro bone MSC (BMSC) viability, alkaline phosphatase (ALP) activity, and gene expression assay results.…”
Section: Introductionmentioning
confidence: 99%
“…Combining biomaterials with osteogenic bioactive molecules has become a widely used approach for BTE because bioactive factors play a significant role in the process of bone regeneration. Growth factors, synthetic peptides, vitamins (D 3 and K), drugs, and other bioactive substances were employed for bone regeneration in conjunction with nHAp scaffolds . One study demonstrated that the sustained delivery of growth factors increased the production of factors linked to osteogenic differentiation in poly­(lactide- co -glycolide) (PLGA) microspheres loaded with vascular endothelial growth factors and bone morphogenic protein-2 (BMP-2) containing collagen and n-HAp .…”
Section: Introductionmentioning
confidence: 99%
“…It offers improved osseointegration, biocompatibility, and controlled drug release. It can also be used as coatings for implants and in biosensors for early disease detection [21].…”
Section: Introductionmentioning
confidence: 99%